Risk assessment, prognosis and guideline implementation in pulmonary arterial hypertension. Issue 2 (3rd August 2017) - Boucly, Athénaïs; Weatherald, Jason; Savale, Laurent; Jaïs, Xavier; Cottin, Vincent; Prevot, Grégoire; Picard, François; de Groote, Pascal; Jevnikar, Mitja; Bergot, Emmanuel; Chaouat, Ari; Chabanne, Céline; et al.
Current European guidelines recommend periodic risk assessment for patients with pulmonary arterial hypertension (PAH). The aim of our study was to determine the association between the number of low-risk criteria achieved within 1 year of diagnosis and long-term prognosis. Incident patients with idiopathic, heritable and drug-induced PAH between 2006 and 2016 were analysed. The number of low-risk criteria present at diagnosis and at first re-evaluation were assessed: World Health Organization (WHO)/New York Heart Association (NYHA) functional class I or II, 6-min walking distance (6MWD) >440 m, right atrial pressure <8 mmHg and cardiac index ≥2.5 L·min −1 ·m −2 . 1017 patients were included (mean age 57 years, 59% female, 75% idiopathic PAH). After a median follow-up of 34 months, 238 (23%) patients had died. Each of the four low-risk criteria independently predicted transplant-free survival at first re-evaluation. The number of low-risk criteria present at diagnosis (p<0.001) and at first re-evaluation (p<0.001) discriminated the risk of death or lung transplantation. In addition, in a subgroup of 603 patients with brain natriuretic peptide (BNP) or N-terminal pro-brain natriuretic peptide (NT-proBNP) measurements, the number of three noninvasive criteria (WHO/NYHA functional class, 6MWD and BNP/NT-proBNP) present at first re-evaluation discriminated prognostic groups (p<0.001). A simplified risk assessment tool that quantifies the number of low-risk criteria present accurately predicted transplant-free survival in PAH. Simplified risk assessment using the number of low-risk criteria predicts prognosis at baseline and follow-up in PAH http://ow.ly/KMsj30cPNbm